2010
DOI: 10.2355/isijinternational.50.469
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Recrystallization and Subsequent Microstructural Evolution during Intercritical Annealing in Cold-rolled Low Carbon Steels

Abstract: Fig. 11. Schematics of the microstructural evolution during intercritical annealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 17 publications
5
42
1
Order By: Relevance
“…It was shown in a previous study, 52) that the recrystallization behavior of this material is quite unlike the one of a conventional cold-rolled dual-phase steel. 53) This is a result of the low dislocation density in the warm deformed ferrite which retards recrystallization. It was concluded from detailed microstructure and texture evaluations that grain growth prevails over recrystallization.…”
Section: Grain Size Stabilitymentioning
confidence: 99%
“…It was shown in a previous study, 52) that the recrystallization behavior of this material is quite unlike the one of a conventional cold-rolled dual-phase steel. 53) This is a result of the low dislocation density in the warm deformed ferrite which retards recrystallization. It was concluded from detailed microstructure and texture evaluations that grain growth prevails over recrystallization.…”
Section: Grain Size Stabilitymentioning
confidence: 99%
“…The sample heated at 10°C/s showed a partially recrystallized matrix, whereas the number of recrystallized grains was very low in the sample heated at 200°C/s. A previous study 18) showed that the hardness curve shifted markedly to higher temperatures if the sample is fully recrystallized using a preheat treatment before any continuous heating occurs. However, the same study 18) also showed that the hardness curve of a recrystallized sample shifts toward higher temperatures with increasing heating rate, because an increasing heating rate shortens the time for any formation of austenite.…”
Section: Microstructural Observations and Microhardness Measurementsmentioning
confidence: 99%
“…A previous study 18) showed that the hardness curve shifted markedly to higher temperatures if the sample is fully recrystallized using a preheat treatment before any continuous heating occurs. However, the same study 18) also showed that the hardness curve of a recrystallized sample shifts toward higher temperatures with increasing heating rate, because an increasing heating rate shortens the time for any formation of austenite. In the case of recrystallized samples, the shift in the hardness curve toward higher temperatures was around 25°C on increasing the heating rate from 10°C/s to 200°C/s.…”
Section: Microstructural Observations and Microhardness Measurementsmentioning
confidence: 99%
“…The role of the carbide particles, Crcarbides in particular, should be taken into account too. During intercritical annealing, a complex interaction between recrystallization, grain growth, and phase transformation occurs 9,10 . The degree of such interplay depends, first of all, on the chemical composition of the steel (e.g., microalloying additions) and processing parameters 8,11,12 .…”
Section: Introductionmentioning
confidence: 99%